MELIHAT SISTEM PEREKONOMIAN INDONESIA DENGAN PERSPEKTIF ISLAM - NAZERI NAZERI (JEBI (Jurnal Ekonomi dan Bisnis Islam), 2016)
The economic system is the process provide income to people's lives, both in the long term and short term. What is wrong with the economic system of Indonesia? Is the government does not pay attention to the public? In theory an economic system that consists of a capitalist, socialist and Islamic system. In its application in Indonesian economic system over the capitalist system tends to apply. Judging from policies issued sometimes more aligned to the owners of capital. Sources of more production controlled by private parties and foreign parties, so that the uneven distribution of income.